External load of Flamenco Zap-3 footwork test: Use of PlayerLoad Concept with triaxial accelerometry - Zhang, N.; Gómez-Lozano, S.; Armstrong, R.; Liu, H.; Vargas-Macías, A. (Sensors, 2022)
The intense footwork required in flamenco dance may result in pain and injury. This study aimed to quantify the external load of the flamenco Zapateado-3 (Zap-3) footwork via triaxial accelerometry in the form of PlayerLoad (PL), comparing the difference in external loads at the fifth lumbar vertebra (L5), the seventh cervical vertebra (C7) and the dominant ankle (DA), and to explore whether the speed, position, axis and proficiency level of the flamenco dancer affected the external load. Twelve flamenco dancers, divided into professional and amateur groups, completed a 15-s Zap-3 footwork routine at different speeds. Triaxial accelerometry sensors were positioned at the DA, L5 and C7 and were utilized to calculate the total PlayerLoad (PLTOTAL), uniaxial PlayerLoad (PLUNI) and uniaxial contributions (PL%). For both PLTOTAL and PLUNI, this study identified significant effects of speed and position (p < 0.001), as well as the interaction between speed and position (p = 0.001), and at the DA, values were significantly higher (p < 0.001) than those at C7 and L5. Significant single axis and group effects (p < 0.001) and effects of the interactions between the position and a single axis and the group and speed (p = 0.001) were also identified for PLUNI. Medial-lateral PL% represented a larger contribution compared with anterior-posterior PL% and vertical PL% (p < 0.001). A significant interaction effect of position and PL% (p < 0.001) also existed. In conclusion, the Zap-3 footwork produced a significant external load at different positions, and it was affected by speed, axis and the proficiency level of the flamenco dancer. Although the ankle bears the most external load when dancing the flamenco, some external load caused by significant vibrations is also borne by the lumbar and cervical vertebrae.